Aspen forests on the Uncompahgre Plateau: current and future expectations - Alsanousi, Attia A. Mussa, author; Binkley, Daniel, advisor; Smith, Frederick W., committee member; Sibold, Jason S., committee member (Colorado State University. Libraries, 2012)
Dynamic changes in aspen cover on the Uncompahgre Plateau have raised concerns among researchers and communities about the stability and long-term survivorship of aspen forests. In the summer of 2010, aspen increment cores were measured for current age distribution from sixty-three random locations across the Plateau including pure aspen and mixed conifer- aspen stands, to provide insights about aspen forests in the near future. Most of aspen trees on the Plateau in 2010 were 100 to 130 years old, and having established after the last major landscape-scale fire in 1879. Trees older than 140 years accounted for about 2% of all stems, with the oldest tree in our random sample being 272 years at breast height. Aspen cover will likely decline over the next five decades, as young cohorts (<80 years) have fewer stems than older cohorts (100- 130 years). Several ecological processes or events could accelerate aspen decline, including conifer replacement of aspens in mixed stands and severe drought. The three survivorship scenarios showed that the reduction in aspen cover by 2060 will likely vary from about 40% of current aspen cover in the most optimistic scenario to a 84% reduction in a higher mortality scenario. The Plateau currently has abundant numbers of aspen suckers, but few of these escape browsing pressure to become trees. The aspen decline predicted in the scenarios may continue beyond 2060 if recruitment remains low, or could be turned around if widespread disturbance regenerates forests, or if browsing pressure drops substantially.
Keywords: age; aspen; forest; reduction; survivorship; Uncompahgre